Ghrelin regulates the proliferation and apoptosis of high glucose‐induced islet cells through the PI3K–Akt signaling pathway. (30th January 2023) - Zang, Pu; Yang, Cuihua; Lei, Haiyan; Guo, Qingyu; Wang, Wei; Shao, Jiaqing
Abstract: Ghrelin may have therapeutic value in mitigating insulin resistance and type 2 diabetes, based on which we further explore the action mechanism of ghrelin on islet cells in this research. In the course of experiments, MIN6 cells were induced by glucose and then treated with acylated or unacylated ghrelin. The effects of ghrelin on the viability, proliferation, apoptosis, and insulin release of high glucose‐induced islet cells were detected by Cell Counting Kit‐8, 5‐ethynyl‐2′‐deoxyuridine, flow cytometry, and enzyme‐linked immunosorbent assays, respectively. Meanwhile, cells were treated with LY294002 to explore whether and how the inhibited phosphoinositide 3‐kinase–protein kinase B (PI3K–AKT) signaling pathway participated in the internal mechanism of ghrelin‐regulating islet cells. Western blotting was performed to quantify the expression levels of Bcl‐2, Bax, Cleaved caspase‐3, PI3K, and AKT. As a result, ghrelin alleviated high glucose‐induced suppression of viability and proliferation and promotion on apoptosis of MIN6 cells. Ghrelin also attenuated the inhibitory effects of high glucose on expression levels of PI3K–Akt signaling axis‐related proteins and insulin release in MIN6 cells. Besides, ghrelin weakened the impacts of high glucose on boosting MIN6 cell apoptosis and hindering proliferation through the PI3K–Akt signaling axis. Collectively, ghrelin regulates the proliferation and apoptosis of high glucose‐induced islet cells through the PI3K–Akt signaling pathway.